A disease‐associated missense mutation in CYP4F3 affects the metabolism of leukotriene B4 via disruption of electron transfer. Issue 4 (9th June 2022) - Smeets, Elien; Huang, Shengyun; Lee, Xiao Yin; Van Nieuwenhove, Erika; Helsen, Christine; Handle, Florian; Moris, Lisa; El Kharraz, Sarah; Eerlings, Roy; Devlies, Wout; Willemsen, Mathijs; Bücken, Leoni; et al.
Abstract: Background: Cytochrome P450 4F3 (CYP4F3) is an ω‐hydroxylase that oxidizes leukotriene B4 (LTB4), prostaglandins, and fatty acid epoxides. LTB4 is synthesized by leukocytes and acts as a chemoattractant for neutrophils, making it an essential component of the innate immune system. Recently, involvement of the LTB4 pathway was reported in various immunological disorders such as asthma, arthritis, and inflammatory bowel disease. We report a 26‐year‐old female with a complex immune phenotype, mainly marked by exhaustion, muscle weakness, and inflammation‐related conditions. The molecular cause is unknown, and symptoms have been aggravating over the years. Methods: Whole exome sequencing was performed and validated; flow cytometry and enzyme‐linked immunosorbent assay were used to describe patient's phenotype. Function and impact of the mutation were investigated using molecular analysis: co‐immunoprecipitation, western blot, and enzyme‐linked immunosorbent assay. Capillary electrophoresis with ultraviolet detection was used to detect LTB4 and its metabolite and in silico modelling provided structural information. Results: We present the first report of a patient with a heterozygous de novo missense mutation c.C1123 > G;p.L375V in CYP4F3 that severely impairs its activity by 50% ( P < 0.0001), leading to reduced metabolization of the pro‐inflammatory LTB4. Systemic LTB4 levels (1034.0 ± 75.9 pg/mL) are significantly increased compared with healthy subjects (305.6 ± 57.0 pg/mL, P < 0.001), and immune phenotyping shows increased total CD19+ CD27− naive B cells (25%) and decreased total CD19+ CD27+ IgD− switched memory B cells (19%). The mutant CYP4F3 protein is stable and binding with its electron donors POR and Cytb5 is unaffected ( P > 0.9 for both co‐immunoprecipitation with POR and Cytb5). In silico modelling of CYP4F3 in complex with POR and Cytb5 suggests that the loss of catalytic activity of the mutant CYP4F3 is explained by a disruption of an α‐helix that is crucial for the electron shuffling between the electron carriers and CYP4F3. Interestingly, zileuton still inhibits ex vivo LTB4 production in patient's whole blood to 2% of control ( P < 0.0001), while montelukast and fluticasone do not (99% and 114% of control, respectively). Conclusions: A point mutation in the catalytic domain of CYP4F3 is associated with high leukotriene B4 plasma levels and features of a more naive adaptive immune response. Our data provide evidence for the pathogenicity of the CYP4F3 variant as a cause for the observed clinical features in the patient. Inhibitors of the LTB4 pathway such as zileuton show promising effects in blocking LTB4 production and might be used as a future treatment strategy.